Wireless power transfer system for a human motion energy harvester - Pillatsch,P; Yeatman,EM; Holmes,AS; Wright,PK (Sensors and Actuators A: Physical, 2016)
Human motion energy harvesting as an alternative to battery powering in body worn and implanted devices is challenging during prolonged periods of inactivity. Even a buffer energy storage system will run out of power eventually if there is no external acceleration to the harvester. This paper presents a method to actuate the rotor inside a previously presented rotational piezoelectric energy harvester wirelessly via a magnetic reluctance coupling to an external driving rotor with one or more permanent magnet stacks attached. This makes it possible to recharge a battery or super-capacitor even if a patient is not moving. The use of a permanent magnet coupling has potential advantages compared to traditional inductive or ultrasonic methods, e.g. in terms of tissue damage and transmission depth. Simulation results show the achievable coupling torque for different configurations of magnet geometries and relative positions between the driving magnet stack(s) and the harvester. It is shown that using a single magnet stack yields better results than using two diametrically opposite stacks. Measurements are performed with different magnets, driving frequencies and orientations of the harvester. The results are discussed and successful energy transfer was achieved regardless of the orientation of the device with respect to gravity, which is desirable for real world applications. Lateral misalignment between the harvester and the driving magnet can also be overcome. The largest distance of power transfer reached was 32 mm with the largest magnets tested, and the optimal power output into a resistive load was over 100 μW at a frequency of 25 Hz. The functional volume of the harvester is 1.85 cm3 – similar to the size of a wristwatch.